2020
DOI: 10.1093/ibd/izaa203
|View full text |Cite
|
Sign up to set email alerts
|

Status of Gene Methylation and Polymorphism in Different Courses of Ulcerative Colitis and Their Comparison with Sporadic Colorectal Cancer

Abstract: Background The objective of this study is to explore the common genetic and epigenetic mechanism of ulcerative colitis (UC) and sporadic colorectal cancer (SCRC) by observing genes methylation level and single nucleotide polymorphisms (SNPs) of different disease courses in UC and SCRC. Methods Two hundred subjects were enrolled, including 40 in the healthy control (HC) group, 50 in the short disease course UC group (SUC), 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Comparison of the IL-1β (-31C>T) genotype frequencies between CRC cases and healthy controls showed that carriers of the C/T genotype were at much higher risk of developing CRC. Data in the literature are few and contradictory and a recent multi-population cohort metaanalysis found a significant association with the dominant model (C/C + C/T vs T/T) and in the heterozygous model (C/T vs T/T) with a reduced risk of developing CRC [32], while research conducted in northeastern Scotland showed that C/C genotype carriers are at higher risk of developing CRC than other genotype carriers [33].Other Indian and Chinese reports did not identify any significant associations at all [34][35][36]. Moreover, IL-1β-31C/T variants were linked to various neoplasms, and the T/T genotype was reported to be associated with an increased risk of hepatocellular [5], gastric [23] and lung cancers [21].…”
Section: Discussionmentioning
confidence: 90%
“…Comparison of the IL-1β (-31C>T) genotype frequencies between CRC cases and healthy controls showed that carriers of the C/T genotype were at much higher risk of developing CRC. Data in the literature are few and contradictory and a recent multi-population cohort metaanalysis found a significant association with the dominant model (C/C + C/T vs T/T) and in the heterozygous model (C/T vs T/T) with a reduced risk of developing CRC [32], while research conducted in northeastern Scotland showed that C/C genotype carriers are at higher risk of developing CRC than other genotype carriers [33].Other Indian and Chinese reports did not identify any significant associations at all [34][35][36]. Moreover, IL-1β-31C/T variants were linked to various neoplasms, and the T/T genotype was reported to be associated with an increased risk of hepatocellular [5], gastric [23] and lung cancers [21].…”
Section: Discussionmentioning
confidence: 90%